2021
DOI: 10.1088/1748-3190/ac1711
|View full text |Cite
|
Sign up to set email alerts
|

Biohybrid generators based on living plants and artificial leaves: influence of leaf motion and real wind outdoor energy harvesting

Abstract: Plants translate wind energy into leaf fluttering and branch motion by reversible tissue deformation. Simultaneously, the outermost structure of the plant, i.e. the dielectric cuticula, and the inner ion-conductive tissue can be used to convert mechanical vibration energy, such as that produced during fluttering in the wind, into electricity by surface contact electrification and electrostatic induction. Constraining a tailored artificial leaf to a plant leaf can enhance oscillations and transient mechanical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Thus, also without rectifying the single signals such as by installing a diode bridge at each leaf (which was done in our previous prototypes 5,23 ), here, energy harvesting with positive power balance was possible. The model in Fig.…”
Section: Papermentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, also without rectifying the single signals such as by installing a diode bridge at each leaf (which was done in our previous prototypes 5,23 ), here, energy harvesting with positive power balance was possible. The model in Fig.…”
Section: Papermentioning
confidence: 99%
“…Advances in the understanding of material properties, biochemical mechanisms, and physical processes in artificial and biological matter have shown that living organisms and especially living plants can be exploited for energy conversion [1][2][3][4][5][6] and environmental sensing [7][8][9][10][11][12][13][14] by interfacing and modifying the plants with engineered materials and electronics that enable to turn them into ''devices''. [15][16][17][18] Plant-integrated solutions like light-emitting plants, 19 planthybrid sensing platforms, [7][8][9][10][11][12][13][14] plant-internal electronic circuits, 20,21 and plant-hybrid robotics, 22 as well as living plantdriven energy harvesting 1-3 using wind, 5,23 rain drops, 4 the root/ soil microbiome, [24][25][26][27] sap components, [28][29][30] temperature gradients, 31 and potential differences between soil and plant 32 endow great prospects for connecting plants to man-made technology and for sustainable concepts to derive novel energyautonomous devices, for example for environmental monitoring, in agriculture, climate change surveillan...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such devices are either permanently or transiently fixed on a plant leaf where they perform a specific task and have a potential impact on monitoring and preserving plants and ecosystems. Examples are sensors that measure plant parameters ( Khan et al., 2018 ; Jiang et al., 2020 ; Diacci et al., 2021 ; Fiorello et al., 2021 ; Dufil et al., 2022 ); molecule delivery platforms ( Fiorello et al., 2021 ); robots and drones that could use a plant or a leaf as support ( Graule et al., 2016 ; Fiorello et al., 2021 ; Jiaming et al., 2021 ), and, moreover, energy harvesting artificial leaves ( Jie et al., 2018 ; Meder et al., 2018 ; Meder et al., 2020a ; Wu et al., 2020 ; Meder et al., 2021 ; Meder et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The latter have recently been shown to be capable of converting wind into electrical energy: the artificial leaves installed on plant leaves exploit the wind-induced leaf oscillations and fluttering for a mechanical-to-electrical energy conversion ( Meder et al., 2020a ; Meder et al., 2021 ). In more detail, the motion of the artificial leaf fixed firmly on the petiole of the natural leaf causes the two surfaces to contact and separate due to air flow.…”
Section: Introductionmentioning
confidence: 99%